2017
DOI: 10.1002/wsb.745
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal distance sampling all‐terrain vehicle surveys for nonbreeding rails

Abstract: Rails (Family: Rallidae) are among the most difficult birds to detect. Although methods have been developed to optimize detection during the breeding season, there is no current suitable survey method for the nonbreeding season. Low detection of rails and lack of suitable methods limit monitoring efforts and examination of important questions related to rail conservation and habitat management during the nonbreeding season. We present a new survey method along with suggestions for its effective use in moistsoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Our study provides missing information that can be used to implement direct conservation and management actions, namely the active flooding of wetlands, in a way that maximizes the benefit to migratory waterbirds, including rails. While closely related species are often described as having similar characteristics, we show here that these two rails have different habitat needs than each other and different migratory timing than each other and Sora [18]. Understanding these differences is vital to the conservation and management of all rails as well as their wetland communities.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Our study provides missing information that can be used to implement direct conservation and management actions, namely the active flooding of wetlands, in a way that maximizes the benefit to migratory waterbirds, including rails. While closely related species are often described as having similar characteristics, we show here that these two rails have different habitat needs than each other and different migratory timing than each other and Sora [18]. Understanding these differences is vital to the conservation and management of all rails as well as their wetland communities.…”
Section: Discussionmentioning
confidence: 72%
“…We surveyed wetlands that spanned from dry to 50 cm water depth, so we doubt water depth influenced our ability to detect Virginia Rails. We assessed this concern using radio-tagged Sora, and found that marked Sora did not run away from the approaching ATV [18] but future study is needed to understand the behavioral reaction of Virginia Rails to approaching ATVs at night using radio-marked birds. Because there are no formal population estimates for Virginia Rails and Sora we are unable to further infer differences between species abundances in our counts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations